1931
DOI: 10.1084/jem.53.3.413
|View full text |Cite
|
Sign up to set email alerts
|

I. Effects of the Intravenous Injection of Colloidal Silver Upon the Hematopoietic System in Dogs

Abstract: 1. Colloidal silver has no specific action on the bone marrow in dogs but is a systemic poison which may cause anorexia, weakness, loss of weight, anemia, and death. 2. Hemolysis can be demonstrated after large doses of colloidal silver and the anemia presumably is due in part at least to a destruction of red blood cells in the peripheral circulation. 3. The colloidal silver, injected intravenously, is deposited as granules almost exclusively in the cells of the reticulo-endotheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1961
1961
2019
2019

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Just as the use of specifically produced nanoparticles is relatively old, the history of nanotoxicology began long before this discipline received its name. In this context, reference is made to publications on the study of nano‐silver , nano iron oxides or titanium dioxide in nanoscale , to name only a few. In addition, there are decades of experience in environmental toxicology with regards to workplace and environmental pollution with dust, fine dust, and ultra‐fine dust, resulting in, e.g., threshold limit values (TLV) (German MAK values) or even European limit values.…”
Section: Nanotoxicology: Is It Really a New Discipline?mentioning
confidence: 99%
“…Just as the use of specifically produced nanoparticles is relatively old, the history of nanotoxicology began long before this discipline received its name. In this context, reference is made to publications on the study of nano‐silver , nano iron oxides or titanium dioxide in nanoscale , to name only a few. In addition, there are decades of experience in environmental toxicology with regards to workplace and environmental pollution with dust, fine dust, and ultra‐fine dust, resulting in, e.g., threshold limit values (TLV) (German MAK values) or even European limit values.…”
Section: Nanotoxicology: Is It Really a New Discipline?mentioning
confidence: 99%
“…The hematological effects of intravenous colloidal silver infusions were studied by the Nobel Laureate, Dr George H. Whipple. In 1930‐1931, he infused multiple dogs with colloidal silver in a fashion similar to our three patients . Prior animal studies suggested to him that the causal mechanism for silver‐induced anemia might be induction of bone marrow aplasia, a model he was seeking in the study of human aplastic anemia.…”
Section: Discussionmentioning
confidence: 74%
“…No chelating agents have yet proven useful in remitting silver toxicity, and this includes more recently introduced products such as dimercaptosuccinic acid (Succimer), useful in lead poisoning . The mechanism resulting in anemia consequent to intravenous silver infusion is, in large part, due to accelerated, persistent, and profound copper and perhaps zinc excretory losses promoted by the elevated serum silver levels . Leukopenia and neutropenia may also be present but seem less of a clinically important issue than the anemia.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations